Erratum: Accelerated thermal cycle and chemical stability testing of Polyethylene glycol (PEG) 6000 for solar thermal energy storage (Solar Energy Materials and Solar Cells (2016) 147 (235-239) DOI: 10.1016/j.solmat.2015.12.023) - Sharma R.K.; Ganesan P.; Tyagi V.V.; Mahlia T.M.I.; Mehrali M. (Elsevier, 2023)
[No abstract available]